Future Changes in Human-Biometeorological Index Classes in Three Regions of Luxembourg, Western-Central Europe - Hanna Leona Lokys; Jürgen Junk; Andreas Krein (Advances in Meteorology)
Projected climate change will cause increasing air temperatures affecting human thermal comfort. In the highly populated areas of Western-Central Europe a large population will be exposed to these changes. In particular Luxembourg—with its dense population and the large cross-border commuter flows—is vulnerable to changing thermal stress. Based on climate change projections we assessed the impact of climate change on human thermal comfort over the next century using two common human-biometeorological indices, the Physiological Equivalent Temperature and the Universal Thermal Climate Index. To account for uncertainties, we used a multimodel ensemble of 12 transient simulations (1971–2098) with a spatial resolution of 25 km. In addition, the regional differences were analysed by a single regional climate model run with a spatial resolution of 1.3 km. For the future, trends in air temperature, vapour pressure, and both human-biometeorological indices could be determined. Cold stress levels will decrease significantly in the near future up to 2050, while the increase in heat stress turns statistically significant in the far future up to 2100. This results in a temporarily reduced overall thermal stress level but further increasing air temperatures will shift the thermal comfort towards heat stress.